EVALUATION OF ROCK MASS CLASSIFICATION IMPLEMENTATION AT TUNNEL ACCESS ROAD BETWEEN TANANTOVEA, DONGGALA DISTRICT AND NORTH PARIGI, PARIGI MOUTONG DISTRICT, CENTRAL SULAWESI - HARTOYO (NIM: 22014017), THIO
Tawaeli-Toboli road as a pillar of economic western and eastern parts of Central Sulawesi is located on hilly terrain, so it tends winding road with steep side slopes. This makes distance of road becomes longer and vulnerable to falling rocks on roadside, therefore it is necessary to make tunnel at some points on the road. Generally, research area is located at structural steep hill geomorphology unit. Tunnel excavation is at Paleozoic Metamorphic Formation composed of schist and gneiss with jointed condition. In research area, empirical methods of rock mass classification RMR, Q-System, GSI and RSR are used to determine rock mass class. Results analyses of rock mass classification along tunnel plan, RMR value range from 43.6 - 56 (III. fair), Q-System value range from 0.535 - 1.383 (poor to very poor), GSI value range 45 - 50 (blocky, poor to fair), and RSR value range from 46.8 – 62.5 (fair to good). Rock mass class obtained in each classification produce design of tunnel reinforcement as shotcrete, fibre concrete, steel ribs, rockbolt, and wiremesh. In addition, also obtained engineering properties of rock masses such as cohesion range from 180 - 570 kPa, deformation modulus range from 3.1 - 5.2 GPa, friction angle range from 30o - 42o, and tensile strength range from 0.08 - 0.72 MPa that are used as inputs into tunnel stability analysis using finite element method. Additionally, input data used in analysis is load design used as overburden loads with range 0.765 – 2.181 MPa and peak ground acceleration of 0.6g from historical earthquakes as seismic loads. The analysis results of rock mass classification were produced strength factor with value from 0.63 - 4.42 and displacement with value from 0.8 - 5.1 mm. The analysis results were evaluated to determine rock mass classification according to the condition of tunnel. From the results of evaluation, RMR provides a more accurate reinforcement design in the inlet and outlet, and then Q-System provides a more accurate reinforcement design in as tunnel.